Analisis Perlakuan Akuntansi berdasarkan SAK Indonesia untuk UMKM studi kasus pada X-Barue Coffee Banyuwangi - Diana Dwi Astuti; Sherly Aulia Zahra; Wiwik Fitria Ningsih (Relasi : Jurnal Ekonomi, 2024)
-Barue Coffee is an MSME that operates in the coffee management sector located in Kalibaru, Banyuwangi. Coffee is a plantation commodity that has a harvest period once a year, so financial management is very important in the running of this business. Good financial management must start from proper recording and quality financial reports in order to provide clear and complete financial information, and support appropriate decision making. Recording must refer to applicable accounting standards, namely the Indonesian Financial Accounting Standards for Micro, Small and Medium Entities (EMKM). This research aims to (1) analyze accounting accounting in recording transactions (2) understand in depth the financial management of X-Barue Coffee MSMEs. The method used in this research uses a qualitative method with a case study approach, data is collected through observation and interviews. The sample collection technique uses purposive sampling. The research results show that X-Barue Coffee MSMEs still use simple manual recording methods, are not in accordance with Indonesian SAK for EMKM, and there is a mixture of personal and business wealth. In financial management, X-Barue Coffee concerns planning, recording, reporting and financial control, but it is still not optimal according to the established standards.